Risk Management Analysis in the Implementation of Building Construction Projects - Titin Rahayuningsih; Laksono Djoko Nugroho; Haris Muhammadun (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research aims to identify risks and determine responses to risks that can affect the implementation of the Bojonegoro Regency Oncology Specialised Hospital Construction Project Phase 2. The research was conducted using literature study and field study methods. Primary data was obtained through documentation, field surveys, and interviews, while secondary data included the Cost Budget Plan (RAB), project schedule, and weekly project reports. Sampling was conducted using the Slovin technique to obtain a representative number of respondents. The results showed that there were 31 relevant risk variables, grouped into 8 categories, namely force majeure, material, equipment, labour, contractual, construction, design and technology, and management risks. Significant risks were identified using the Severity Index method, which measures probability and time impact. The results of the risk analysis using the severity index method showed that there were 24 risks included in the low risk level, 3 risks included in the medium risk level, and 2 risks included in the high risk level.